Kropparnas poesi: Om Eva Runefelt, Eva Ström och det sena 1970-talets poesi - Bojö, Anna-Klara (Tidskrift för litteraturvetenskap, 2021)
The Bodies’ Poetry: Eva Runefelt, Eva Ström and Swedish Poetry in the Late 1970’s In the mid 1970’s a new type of poetry, associated with the body, emerged in Sweden. Especially young women writers appeared to take Swedish poetry in new aesthetic directions, exploring questions regarding experience and language. This article focuses on two prominent writers, Eva Runefelt and Eva Ström, and discusses how their different types of poetry can be said to be a bodies’ poetry, and how it was discussed in contemporary literary critique. It also reflects on why this strand of poetry has been granted such a peripheral place in literary history.